2015
DOI: 10.1364/ol.40.003352
|View full text |Cite
|
Sign up to set email alerts
|

200  kHz 55  W Yb^3+: YVO_4-based chirped-pulse regenerative amplifier

Abstract: A chirped-pulse regenerative amplifier based on a Yb:YVO4 (Yb:YVO) crystal was demonstrated for the first time, to our knowledge. A novel wavelength-independent off-axis technique was used to deliver 26.6 W of pump power with a low quantum defect. It was seeded by means of a 120 fs Yb:YVO4 oscillator. It generates as much as 5.5 W of average output power with chirped pulses and 4.2 W with 200 fs compressed pulses at a 200 kHz repetition rate. A maximum pulse energy of 140 μJ was obtained at pulse repetition fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, so far there is not one kind of electro-optic crystal or configuration the can provide a general solution under different operating wavelengths, repetition rates, spot diameters, and output powers. At present, BBO crystal Pockels cells with minimal piezoelectric ringing and low acoustic noise, have emerged in high repetition rate (>100 kHz) pulse picking applications [14][15][16][17]19]. Nevertheless, with the increase of repetition rate, it is difficult to realize fast switching within the effective duty cycle due to the long fall time of the high voltage.…”
Section: Experimental Principle and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…However, so far there is not one kind of electro-optic crystal or configuration the can provide a general solution under different operating wavelengths, repetition rates, spot diameters, and output powers. At present, BBO crystal Pockels cells with minimal piezoelectric ringing and low acoustic noise, have emerged in high repetition rate (>100 kHz) pulse picking applications [14][15][16][17]19]. Nevertheless, with the increase of repetition rate, it is difficult to realize fast switching within the effective duty cycle due to the long fall time of the high voltage.…”
Section: Experimental Principle and Setupmentioning
confidence: 99%
“…Determined by the parameters of Pockels cell and regenerative cavity, repetition rates from hundreds to mega-Hz have been obtained with output power up to 100 watts. For instance, Nd:YVO 4 picosecond regenerative amplifiers with a repetition rate up to 850 kHz have been demonstrated [14,15]; other broadband gain materials such as Yb:CaF 2 , Yb:CAlGO, Yb:YVO 4 , and Nd:LuVO 4 show up to 1.43 MHz repetition rate [16][17][18]. Currently, Bergmann et al [19] reported the record high repetition rate of 2 MHz for a picosecond regenerative amplifier in Yb:YAG.…”
Section: Introductionmentioning
confidence: 99%
“…In case of Yb:YAG, the peak of the gain is centered around 1030 nm, and the systems could easily be seeded by fiber or solidstate-based Yb oscillators [6][7][8]. For other Yb-amplifier systems like Yb:YVO 4 [9,10], Yb:CaF 2 [11], Yb:KYW [12], Yb:YLF [13], and Yb:LLF [14,15], the gain spectrum covers regions well below 1030 nm, especially for oscillators that are operated at cryogenic temperatures [16][17][18][19]. As an example, with cryogenic Yb:YLF strong amplification of ns pulses is feasible in the 985-1020 nm range with strong gain peaks located at 992.5 nm, 995.2 nm, 999.7 nm, 1006.2 nm, 1013.2 nm, 1018 nm and 1019.2 nm [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond sources around the 1000 nm region are also interesting as seed sources for Yb-based amplifiers. Popular systems such as Yb:YAG could be efficiently seeded by Yb-fiber seeders, whereas for crystals such as Yb:YVO4 [34], Yb:CaF2 [35], Yb:KYW [36], Yb:YLF [37][38][39], Yb:LLF [40,41], the gain spectra cover regions well below 1030 nm, especially at cryogenic temperatures [42][43][44][45]. Unfortunately, it is rather difficult to develop Yb-fiber based seeders at these shorter wavelengths [46].…”
Section: Introductionmentioning
confidence: 99%